2018
DOI: 10.3390/su10114241
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Coordination, Participation, and Training in Post-Disaster Shelter Projects

Abstract: The delivery of post-disaster shelter assistance continues to be fraught with challenges derived from the coordination of resources, involvement of project stakeholders, and training of households and builders. There is a need to better understand what project elements in the delivery of post-disaster shelter projects most influence resilience and sustainability. To address this need, we examined nineteen post-disaster shelter projects in the Philippines following Typhoon Haiyan. We first characterized coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Recently, QCA has seen increasing application within the international water and sanitation sector research to reveal and characterize the complex drivers of water and sanitation service delivery outcomes, including water and sanitation in schools [28,29], water points [9], sanitation infrastructure [30], and overall service sustainability [31][32][33]. QCA is particularly useful for describing complex causal relationships by analyzing the ways in which conditions combine together to yield an outcome, rather than quantifying the effects of independent variables [34][35][36]. QCA retains the power of rich, in-depth knowledge of cases, while providing more generalizable results from the analysis [37].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, QCA has seen increasing application within the international water and sanitation sector research to reveal and characterize the complex drivers of water and sanitation service delivery outcomes, including water and sanitation in schools [28,29], water points [9], sanitation infrastructure [30], and overall service sustainability [31][32][33]. QCA is particularly useful for describing complex causal relationships by analyzing the ways in which conditions combine together to yield an outcome, rather than quantifying the effects of independent variables [34][35][36]. QCA retains the power of rich, in-depth knowledge of cases, while providing more generalizable results from the analysis [37].…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-six years ago, the UNDRO [17] concluded that the key to success in reconstruction is the local community's participation. Opdyke, Javernick-Will and Koschmann [23] found that early user involvement in PDPC shelter projects, support the resilience and the sustainability of the project outcome. The local input could empower the affected people, encourage the social connectivity and promote solidarity between the beneficiaries themselves [24].…”
Section: Social Environmental and Economic Aspectsmentioning
confidence: 99%
“…Civil infrastructure services include potable and domestic water, safe sewage disposal, electricity, and passable road networks, all with enough capacity and reliability to sustain the community. Housing measures include perceived satisfaction and quality [23]. With growing recognition that relocation requires more than housing, communal infrastructure (e.g., schools and hospitals) have accompanied recent projects [24].…”
Section: Identifying and Measuring Livable Relocation Communitiesmentioning
confidence: 99%
“…Other critical decisions include house design, material selection, community layout, and procedures for implementing the transfer [55,56]. Despite the value of up-front participation in early decisions, participatory approaches are often limited to the inclusion of households in construction [23,57]. Participation in construction generally occurs through sweat equity, which may be required for a new house in lieu of financial equity.…”
Section: Community Involvementmentioning
confidence: 99%
See 1 more Smart Citation